NOTES ON EGGS, LARVAE AND JUVENILES OF FISHES FROM INDIAN WATERS VI. Genus Auxis Cuvier. VII. Sarda orientalis (Terominck & Schlegel - Jones, S (Indian Journal of Fisheries, 2016)
THERE are under this genus two distinct species distinguished mainly by thenature of their corselets. In the first species, A. (hazard the corselet isshort, abruptly constricting immediately behind the vertical from the hindend of the first dorsal, whereas in the second species it gradually tapers andextends to well behind the second dorsal. Bleeker described A. tapeinosoma(Bleeker, 1854), and A. thynnoides (Bleeker,. 1855) from Indonesian watersand these have been relegated as synonyms oi A. thazard by Beaufort (1951).Wade (1949), while working on Philippine tunas, recognised the presenceof a long corseletted form distinct from the short corseletted form and fixedthe identity of the former as A. tapeinosoma, a name used by subsequentworkers (Herre and Herald 1951;Herre, 1953; Jones, 1958). Recently Matsumoto(1959) after a critical study of the original descriptions and examinationof the type specimens of both A. tapeinosoma and A. thynnoides foundthat the former is a short corseletted form and as such is synonymous withA. thazard, while the latter is a long corseletted form